Validation of the Italian versions of the Bath Ankylosing Spondylitis Functional Index (BASFI) and the Dougados Functional Index (DFI) in patients with ankylosing spondylitis - W. Grassi; M. Carotti; A. Silvestri; A. Stancati; F. Salaffi (PAGEPress Publications, 2011)
Objectives: The Bath Ankylosing Spondylitis Functional Index (BASFI) and the Dougados Functional Index (DFI) are the most commonly used instruments to measure functioning in ankylosing spondylitis (AS). The aim of this study was to translate, adapt and validate these instruments into the Italian language. Methods: The BASFI and DFI questionnaires were translated into Italian by two independent bilingual physicians who were familiar with the medical aspects of AS and by one professional translator. Two rheumatologists familiar with instrument validation, and who were aware of the purpose of the study, examined semantic, idiomatic and conceptual issues and produced by consensus unified versions of each instrument. English back-translations from the Italian were done by a professional translator unaware of the original version. Both English versions were compared, and where needed, modifications to the Italian versions were made. Results: A total of 95 patients were included: 77 males, age (mean±SD) 47.9±9.3years, and disease duration 12.4±6.6 years, and 18 females, age 45.9±8.7 years, and disease duration 11.3±8.2 years. Reliability, measured in 23 patients participating a physiotherapy program, showed an acceptable one-week test-retest intraclass correlation coefficient (ICC) - BASFI ICC: 0.91, 95% CI: 0,87-0.94 and DFI ICC: 0.86, 95% CI: 0.83-0.90. The internal consistency was 0.90 (Cronbach's alpha) for the BASFI and 0.87 for the DFI. For validity the functional indices were correlated with the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Metrology Index (BASMI), Bath Ankylosing Spondylitis Patient Global Score (BAS-G), modified Health Assesment Questionnaire (HAQ-S), SF-36 physical component summary (SF-36 PCS), stiffness, pain, physician's assessment of disease activity, Bath AS Radiology Index-total (BASRI-t), erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP). The functional indices (BASFI and DFI) were correlated with each other (p<0.0001) and with activity variables. There was no significant relationship between functional indices and BASRI-t and acute phase reactants. The receiver operating characteristic (ROC) curve analysis indicated that the BASFI ranked superior compared to HAQ-S, (p = 0.019) and SF36 PCS (p = 0.002), but not respect to DFI (p = NS), in distinguishing between patients with high and low disease activity. Conclusions: The Italian versions of the BASFI and DFI showed adequate reliability and validity in patients with AS. Because of psychometric advantages, the BASFI may be preferred in clinical trial settings. However, sensitivity to changes due to drug therapy and/or rehabilitation remains to be determined.